2023
DOI: 10.1111/nph.18713
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting leaf traits across functional groups using reflectance spectroscopy

Abstract: Summary Plant ecologists use functional traits to describe how plants respond to and influence their environment. Reflectance spectroscopy can provide rapid, non‐destructive estimates of leaf traits, but it remains unclear whether general trait‐spectra models can yield accurate estimates across functional groups and ecosystems. We measured leaf spectra and 22 structural and chemical traits for nearly 2000 samples from 103 species. These samples span a large share of known trait variation and represent severa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…The authors used the internal validation procedure described in Kothari et al . (2023b) to train prediction models for fresh‐leaf EWT based on reflectance, transmittance, and absorptance spectra. The retrained models showed similar but (as predicted) slightly better performance compared with the original models for rehydrated EWT.…”
Section: Internal Dessain Lopex Angers No Obs No Comps R 2 Rmse %Rm...mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors used the internal validation procedure described in Kothari et al . (2023b) to train prediction models for fresh‐leaf EWT based on reflectance, transmittance, and absorptance spectra. The retrained models showed similar but (as predicted) slightly better performance compared with the original models for rehydrated EWT.…”
Section: Internal Dessain Lopex Angers No Obs No Comps R 2 Rmse %Rm...mentioning
confidence: 99%
“…
Since its publication, the authors of Kothari et al (2023b) have identified an error in the Supporting Information published alongside their article. In the Supporting Information Methods S1 section, it is stated that both the fresh and the rehydrated mass of all leaf samples were measured.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperspectral instruments are capable of detecting changes in leaf reflectance that are associated with variation in a suite of functional traits, including leaf physical structure; concentrations of pigments, nutrients, nonstructural carbohydrates, and leaf water status (Wang et al ., 2020). The performance and generality of spectroscopy‐based methods varies among function traits – the studies featured here, published in New Phytologist , demonstrated promise in predicting leaf carboxylation capacity, leaf mass per area, and leaf age with spectroscopy‐based models that generalize across sites, species, and canopy positions in tropical forests (Chavana‐Bryant et al ., 2017; Wu et al ., 2017, 2019); across multiple ecological domains in the eastern United States and Canada (Wang et al ., 2020; Kothari et al ., 2023); and across biomes, including Arctic and tropical sites (Serbin et al ., 2019). Furthermore, Yan et al .…”
Section: Integration Of Remote Sensing and Mechanistic Vegetation Modelsmentioning
confidence: 99%
“…newphytologist.com/virtualissues.traits, including leaf physical structure; concentrations of pigments, nutrients, nonstructural carbohydrates, and leaf water status(Wang et al, 2020). The performance and generality of spectroscopybased methods varies among function traitsthe studies featured here, published in New Phytologist, demonstrated promise in predicting leaf carboxylation capacity, leaf mass per area, and leaf age with spectroscopy-based models that generalize across sites, species, and canopy positions in tropical forests(Chavana-Bryant et al, 2017;Wu et al, 2017Wu et al, , 2019; across multiple ecological domains in the eastern United States and Canada(Wang et al, 2020;Kothari et al, 2023); and across biomes, including Arctic and tropical sites(Serbin et al, 2019). Furthermore,Yan et al (2021) demonstrated that spectroscopy-based methods are able to predict leaf carboxylation capacity more accurately, and with more generality across sites, than correlations with a suite of other functional traits.…”
mentioning
confidence: 94%